KERJASAMA GURU BK DENGAN GURU AKIDAH AKHLAK DALAM PENGEMBANGAN KEHIDUPAN KEBERAGAMAAN PESERTA DIDIK DI MTsN MODEL PADANG - Mulyanti, Sri; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2014)
Cooperative between Guidance and Counseling teacher and Aqeedah Morals teacher to develop students religious life, but this case don not implemented fully in MTsN Model Padang. We can see because some problems happen about studens religious life. Actually this problem can be solved by Guidance and Counseling teacher and Aqeedah Morals teacher if they work team. Thatâs reason why researcher do research with purpose for identity. 1) Description form of collaboration between Guidance and Counseling teacher and Aqeedah Morals teacher in indentify students who need the guidance religious of life. 2) Description form of collaboration between Guidance and Counseling teacher and Aqeedah Morals teacher in using tools (mosque and counseling teacher). 3) Description form of collaboration between Guidance and Counseling teacher and Aqeedah Morals teacher in give guidance about students religious life is limited by Akidah Akhlak teacher in Models MTsN Model Padang. This research is about descriptive kuantitative research with population consist of 1360 people are sample. Researcher use a stratified random sampling technique. The instrument used at this reseach is quetionaire. For analysis data use presentaqe formula. Result of research show: 1)s DescriptionÂ form of collaboration between Guidance and Counseling teacher with Aqeedah Morals teacher in indentiying students who require the guidance of religious life are good. 2) Description form of collaboration between Guidance and Counseling teacher and with Aqeedah Morals teacher in in use tools (mosque and counseling room) are good. 3) Description form of collaborative between Guidance and Counseling teacher and with Aqeedah Morals teacher in give guidance religious life is limited in category good. Baset on the resulti of research analysis. So we can make a conclusion that collaborative between Akhlak teacher in develop. Students religious life in MTsNÂ Guidance and Counseling teacher andÂ Aqidah Padang, commonly in good good category.